A Systematic Literature Review on the Challenges and Solutions in Public Transportation for Medium-Sized - Setyawan, Yoga; Imarwan, Manu; Egan, Abiel; Toruan, Erni Sari Lumban; Taufik, Mohammad (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Public transportation in medium-sized cities faces unique challenges that are often overlooked in national policy formulation. Cities like Jatiwangi are experiencing rapid spatial and economic growth, yet this is not matched by the availability of adequate public transportation modes, in terms of infrastructure, services, and policies. This study employs a Systematic Literature Review (SLR) approach to identify the challenges and solutions in developing public transportation in medium-sized cities, based on 100 selected publications from the year 2000 to 2025. A bibliometric analysis was conducted using VOSviewer to map the relationships among keywords and dominant thematic clusters. The results reveal five main clusters reflecting concerns regarding technological integration, urban growth, policy solutions, infrastructure safety, and sustainable mobility. This review emphasizes the importance of a contextual, adaptive, and locally-driven approach to public transport in non-metropolitan cities. These findings are expected to serve as a foundation for more inclusive and efficient transportation policy decisions in the future.